THE IDEAL STUDY MODEL OF LIVING WELL WITH DEMENTIA. (11th November 2018) - Victor, C; Jones, I; Wu, Y; Matthews, F; Nelis, S; Martyr, A; Quinn, C; Clare, L
Abstract: To live well with dementia may be characterised as maximising physical, mental and social wellbeing. In the UK this concept is present in policy documents and reports relating to dementia. This demonstrates a change of focus from concerns with symptoms and 'deficits' to a broader focus on participation and inclusion. The Improving the experience of Dementia and Enhancing Active Life (IDEAL) cohort study uses measures of quality of life, life satisfaction and wellbeing to operationalise living well. We use data from the 1, 550 IDEAL baseline interviews to model how these resources are individually and collectively associated with the ability to live well among people with mild to moderate dementia in community settings. We examine the relationships between the individual domains of psychological characteristics and psychological health, physical fitness and physical health, capitals, assets and resources, managing everyday life with dementia and social location and generated a living well latent factor. Psychological characteristics and psychological health is most strongly associated with living well, followed by physical fitness and physical health, capitals, assets and resources and managing everyday life with dementia and social location. This suggests that living well with dementia might be enhanced through improving psychological and physical health as well as addressing other social factors. Although the greatest gain in living well ratings is likely to be achieved through positive increases in factors within the psychological domain, all five domains, and all individual factors within the five domains, were individually associated with capability to live well with dementia.